2013
DOI: 10.1186/1471-244x-13-14
|View full text |Cite
|
Sign up to set email alerts
|

Psychosomatic syndromes and anorexia nervosa

Abstract: BackgroundIn spite of the role of some psychosomatic factors as alexithymia, mood intolerance, and somatization in both pathogenesis and maintenance of anorexia nervosa (AN), few studies have investigated the prevalence of psychosomatic syndromes in AN. The aim of this study was to use the Diagnostic Criteria for Psychosomatic Research (DCPR) to assess psychosomatic syndromes in AN and to evaluate if psychosomatic syndromes could identify subgroups of AN patients.Methods108 AN inpatients (76 AN restricting sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 75 publications
3
25
1
1
Order By: Relevance
“…However, a recent study used the EQ-5D-3L in in-patients with severe AN (Abbate-Daga et al 2014). In this study, patients' quality of life improved during hospitalization with a mean index score of 0.70 at hospital discharge (Abbate-Daga et al 2014). In our study, we also observed increases towards the end of treatment, but at the end of the 1-year follow-up, the index scores had decreased below the respective baseline values in each group.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…However, a recent study used the EQ-5D-3L in in-patients with severe AN (Abbate-Daga et al 2014). In this study, patients' quality of life improved during hospitalization with a mean index score of 0.70 at hospital discharge (Abbate-Daga et al 2014). In our study, we also observed increases towards the end of treatment, but at the end of the 1-year follow-up, the index scores had decreased below the respective baseline values in each group.…”
Section: Discussionsupporting
confidence: 51%
“…As the validity of the EQ-5D-3L in eating disorders has not been determined we decided to use QALYs only in a sensitivity analysis. However, a recent study used the EQ-5D-3L in in-patients with severe AN (Abbate-Daga et al 2014). In this study, patients' quality of life improved during hospitalization with a mean index score of 0.70 at hospital discharge (Abbate-Daga et al 2014).…”
Section: Discussionmentioning
confidence: 91%
“…In a study on anorexia nervosa (AN) patients [22] , mostly subjects with restricted-type AN, almost half of the patients had DCPR illness denial, associated with lower intensity of problems in body mass index, eating behaviors, and beliefs. A quarter of the restricted-type AN patients had high global severity in terms of body mass index, behaviors, thoughts, and DCPR conditions (high rates of alexithymia, demoralization, health anxiety, and irritable mood, ranging from 85 to 100%).…”
Section: Subtyping Medical Patientsmentioning
confidence: 99%
“…Alexithymia represents the inability to identify, label and describe emotions coupled with difficulties in discriminating between internal states and bodily sensations [11]. Patients affected by AN are likely to show higher alexithymia levels than healthy controls [12,13,14], thus highlighting a suboptimal ability to identify and communicate affective states. …”
Section: Introductionmentioning
confidence: 99%